2002
DOI: 10.1016/s1388-2457(02)00050-0
|View full text |Cite
|
Sign up to set email alerts
|

Electric brain responses to inappropriate harmonies during listening to expressive music

Abstract: Objectives: Recent studies with event-related brain potentials (ERPs) investigating music processing found (early) negativities with righthemispheric predominance as a response to inappropriate harmonies within sequences of chords. The stimuli used in those studies were fairly artificial in order to control the experimental factors (e.g. variations in tempo and loudness were eliminated). This raises the question of whether these ERPs can also be elicited during listening to more naturalistic stimuli.Methods: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 38 publications
5
44
0
1
Order By: Relevance
“…Although expressive and mechanical performances can lead to similar parsing of phrases (Palmer & Krumhansl, 1987), and recent research has found the same electrophysiological markers for music-syntactic processing under both performance conditions, some evoked potentials were nevertheless shown to be enhanced for expressive performance (Koelsch & Mulder, 2002;Koelsch, Kilches, Steinbeis, & Schelinski, 2008). Furthermore, expressive performances have more power to evoke emotions than mechanical renderings (e.g., Chapin, Jantzen, Scott Kelso, Steinberg, & Large, 2010;Viellard, Roy, & Peretz, 2011).…”
Section: N Contrast To Short-term Memory Formentioning
confidence: 98%
“…Although expressive and mechanical performances can lead to similar parsing of phrases (Palmer & Krumhansl, 1987), and recent research has found the same electrophysiological markers for music-syntactic processing under both performance conditions, some evoked potentials were nevertheless shown to be enhanced for expressive performance (Koelsch & Mulder, 2002;Koelsch, Kilches, Steinbeis, & Schelinski, 2008). Furthermore, expressive performances have more power to evoke emotions than mechanical renderings (e.g., Chapin, Jantzen, Scott Kelso, Steinberg, & Large, 2010;Viellard, Roy, & Peretz, 2011).…”
Section: N Contrast To Short-term Memory Formentioning
confidence: 98%
“…180-200 ms maximal über rechts-frontalen Elektroden (daher wurde dieser Effekt als early right anterior negativity, ERAN, bezeichnet; Koelsch, 2005;Koelsch et al , im Druck b). In Experimenten, in denen die Darbietung irregulärer Akkorde nicht vorhersagbar ist, hat dieser Effekt eine längere Latenz, und eine eher fronto-temporale Schädelverteilung (auch als right anterior-temporal negativity, RATN, bezeichnet; Patel et al , 1998;Koelsch & Mulder, 2002).…”
Section: Verarbeitung Musikalischer Syntaxunclassified
“…Using only the sequences depicted in Figure 1A-C transposed to different keys gave us the maximum acoustic control over the musical stimulus (for details, see Koelsch et al, 2007; for studies investigating music processing with more naturalistic stimuli, see, e.g., Koelsch, Kilches, Steinbeis, & Schelinski, 2008;Steinbeis, Koelsch, & Sloboda, 2006;Koelsch & Mulder, 2002).…”
Section: Stimulimentioning
confidence: 99%